2014
DOI: 10.1002/jcph.413
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel: A multifaceted affair

Abstract: Clopidogrel has been the therapy of choice, combined with aspirin, against platelet aggregation in patients at risk of suffering a vascular thrombotic event. Not all patients respond equally to clopidogrel, an observation that has led to searching for a test that, in the clinical setting, could predict patients' "resistance" to therapy. The evidence reveals a complex pharmacokinetic profile for clopidogrel, with multiple players involved, including cytochromes, characteristics of the target tissue, and accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…As a precursor, clopidogrel must pass through the liver cytochrome P450 enzyme to be metabolized into the active product and then play the role of antiplatelet aggregation, among which CYP2C19 plays the most important role. [ 3 ] Studies have demonstrated that the polymorphism of CYP2C19 gene is closely related to the degree of platelet inhibition of clopidogrel, and the extensive metabolizer (EM) type has a higher platelet inhibition rate than the intermediate metabolizer (IM) type and slow metabolizer. [ 4 ] Asians seem to have a higher probability of carrying a loss of function (LOF) CYP2C19 allele (e.g., CYP2C19∗2 or CYP2C19∗3) than persons of either African or Caucasian ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…As a precursor, clopidogrel must pass through the liver cytochrome P450 enzyme to be metabolized into the active product and then play the role of antiplatelet aggregation, among which CYP2C19 plays the most important role. [ 3 ] Studies have demonstrated that the polymorphism of CYP2C19 gene is closely related to the degree of platelet inhibition of clopidogrel, and the extensive metabolizer (EM) type has a higher platelet inhibition rate than the intermediate metabolizer (IM) type and slow metabolizer. [ 4 ] Asians seem to have a higher probability of carrying a loss of function (LOF) CYP2C19 allele (e.g., CYP2C19∗2 or CYP2C19∗3) than persons of either African or Caucasian ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…After numerous studies, some of them supporting a black box warning by the US Food and Drug Administration (FDA), the value of CYP2C19 genotyping previous to clopidogrel administration is still a subject for debate, mostly because (1) ex vivo platelet aggregation assays do not accurately reflect the in vivo response to antiplatelet agents, and (2) there is great heterogeneity in the clinical studies performed to date, as expressed in recent reviews …”
mentioning
confidence: 99%
“…Indeed, the pharmacokinetic and pharmacodynamic parameters of clopidogrel in healthy subjects both seem to be unpredictable based on a single factor, with clinical resistance likely dependent on multiple factors …”
mentioning
confidence: 99%
See 2 more Smart Citations